2013
DOI: 10.1371/journal.ppat.1003276
|View full text |Cite
|
Sign up to set email alerts
|

The Mnn2 Mannosyltransferase Family Modulates Mannoprotein Fibril Length, Immune Recognition and Virulence of Candida albicans

Abstract: The fungal cell wall is the first point of interaction between an invading fungal pathogen and the host immune system. The outer layer of the cell wall is comprised of GPI anchored proteins, which are post-translationally modified by both N- and O-linked glycans. These glycans are important pathogen associated molecular patterns (PAMPs) recognised by the innate immune system. Glycan synthesis is mediated by a series of glycosyl transferases, located in the endoplasmic reticulum and Golgi apparatus. Mnn2 is res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
138
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 109 publications
(144 citation statements)
references
References 62 publications
5
138
1
Order By: Relevance
“…This suggests that glucan exposure and DC phagocytic uptake are not necessarily correlated with cell wall glucan abundance and led to the hypothesis that the molecular structure of mannan may be the major determinant of glucan exposure. Consistent with this hypothesis, previous studies reported the molecular weight of C. albicans N-mannans to be 2.6-fold greater than that of C. glabrata (Hall et al, 2013; West et al, 2013). In addition, the molecular structure of C. glabrata mannan is lower in structural complexity relative to C. albicans (Shibata et al, 2012).…”
Section: Resultssupporting
confidence: 62%
See 3 more Smart Citations
“…This suggests that glucan exposure and DC phagocytic uptake are not necessarily correlated with cell wall glucan abundance and led to the hypothesis that the molecular structure of mannan may be the major determinant of glucan exposure. Consistent with this hypothesis, previous studies reported the molecular weight of C. albicans N-mannans to be 2.6-fold greater than that of C. glabrata (Hall et al, 2013; West et al, 2013). In addition, the molecular structure of C. glabrata mannan is lower in structural complexity relative to C. albicans (Shibata et al, 2012).…”
Section: Resultssupporting
confidence: 62%
“…We began with the CaMNN2 gene family mannosylation mutants previously characterized by Hall et al (2013). This gene family is responsible for normal abundance and complexity of N-mannan side chains (Hall et al, 2013; Rayner and Munro, 1998), and deletion mutant strains of the CaMNN2 family exhibit altered mannan structure. The C. albicans parental strain was compared to the mannosylation mutants mnn2Δ , mnn2Δ /mnn26Δ, and a sextuple mutant (all CaMNN2 gene family deleted).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Glycosylation mostly affects plasma membrane and secreted proteins, and it plays a critical role in regulating many cell-cell interactions (1,3). In pathogenic yeasts, glycosylation has been implicated in host/ pathogen interactions (3,4) and particularly in virulence and immune recognition (5). As protein glycosylation is essential for cell viability in yeast, the glycosylation pathways is a potential target for new anti-fungal drugs.…”
mentioning
confidence: 99%